Energy Transition and Sustainable Road Transportation in Turkey: Multiple Policy Challenges for Inclusive Change - Cevheribucak, Gülfem (Frontiers in Sustainable Cities, 2021)
This paper aims to explore energy insecurity in Turkey at the intersection of environmental sustainability, human security and justice vis-à-vis growing energy demand coupled with greenhouse gas emissions coming from the transport sector. High dependence on fossil fuel imports creates bottlenecks for the economy and require urgent shift to renewable energy sources. Prospects for renewable energy transition are analyzed based on focusing on total final energy consumption by energy and transport sector as well as greenhouse gas emissions. In order to propose holistic clarifications to the triangular problem of high fossil fuel dependence, energy demand increase and greenhouse gas mitigation, sustainable energy transition in road transport is put forward. It is justified based on the share of greenhouse gas emissions originating from road transport sector and high taxation levels that create extra burden on private consumers. Energy transition is conceptualized with the theoretical offerings of sustainability transition literature that point out to socio-technical processes, hence the societal, technological as well as external structural contexts of change. Upon this background, this policy and practice review outlines the current policy instruments in order to highlight the mismatch between policy and practices for just energy transition in conjunction with sustainable mobility in Turkey.